GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 238 species occurrences available in GBIF matching the query: TaxonKey: Solenodon paradoxus Brandt, 1833. The dataset includes 238 records from 22 constituent datasets: 1 records from ISM Mammalogy Collection. 1 records from Zoology (Museum of Evolution - Uppsala). 1 records from KUBI Mammalogy Collection. 83 records from University of Florida Vertebrate Paleontology. 3 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from CRCM Vertebrate Collection. 12 records from Field Museum of Natural History (Zoology) Mammal Collection. 2 records from Lund Museum of Zoology (MZLU). 3 records from Naturalis Biodiversity Center (NL) - Mammalia. 57 records from Museum of Comparative Zoology, Harvard University. 2 records from Mammals housed at MHNG, Geneva. 1 records from UMMZ Mammal Collection. 4 records from Natural History Museum (London) Collection Specimens. 20 records from NMNH Extant Specimen and Observation Records. 1 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 12 records from PSM Vertebrates Collection. 1 records from UAZ Mammals. 5 records from Collection Mammalia SMF. 24 records from AMNH Mammal Collections. 1 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from NMNH Paleobiology Specimen Records. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences